I connect, therefore I am - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
While the techies have been twiddling away with the Internet, and you've been wondering if you'd be left out, the phone has still been getting on with connecting people. Yesterday's future is tantalisingly close, today. Make that call. Send that...